Mediastinal seminoma in the setting of advanced colorectal cancer: beware atypical sites of metastasis. Issue 2 (February 2023) - Wakefield, Craig; Bird, Brian; Doddakula, Kishore; Burke, Louise
Abstract: Primary mediastinal seminoma is an uncommon malignant extragonadal germ cell tumour of the anterior mediastinum occurring almost exclusively in men. We report a case of mediastinal seminoma with prominent follicular lymphoid hyperplasia in a patient with metastatic colorectal cancer and discuss diagnostic considerations including prominent secondary change, immunohistochemical analysis and differential diagnosis.